Examination of macro- and micro elements in the artificial bathwater samples - Lós, Réka; Izbékiné Szabolcsik, Andrea; Ungvári, Csaba; Tóth, Csilla Noémi; Baranyai, Edina; Bodnár, Ildikó (International Journal of Engineering and Management Sciences, 2019)
During our research, micro- and macro element content of synthetically produced bathwater was examined. Previous studies, which were conducted at the Department of Environmental Engineering at the Faculty of Engineering, University of Debrecen, proved that the quality of domestic greywater is greatly varied. This diversity can also be observed in the case of greywaters. The examination of bathwater samples covered the contentanalysis of Al, Ba, Cd, Cr, Cu, Fe, Mn, Ni, Pb, Sr, Zn, Ca, K, Mg, Na, Li elements with the application of MP-AES method. The analysis of greywater’s micro and macro content is essential part in the control of irrigation systems, flushing as well as car washing, because its heavy metal content can have a significant effect on the environment. In this study, we would like to present the concentration values of micro and macro elements of the examined greywater samples. Furthermore, we would like to make a comparison among our result, previously examined greywater samples and drinking water samples, too.